PENGARUH FASILITAS KERJA, PENGAWASAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA KANTOR KEMENTRIAN AGAMA KABUPATEN BANGGAI - Saudin, La; Polim, Adrian (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The aim of this research is to find out whether Work Facilities, Supervision and Compensation partially and simultaneously have a positive and significant effect on Employee Performance at the Banggai Regency Ministry of Religion Office. The research sample is all ASN employees at the Banggai Regency Ministry of Religion Office using purpose sampling techniques with total of 30 people. Data collection methods use interviews and questionnaires. Data were analyzed descriptively quantitatively using frequency tables and multiple linear regression with 3 predictors. Results of data processing carried out using the SPSS version 25.0 program. From the results of the t test, it was found that all independent variables, namely Work Facilities (X1), Supervision (X2) and Compensation, had a partial influence on Employee Performance (Y) at the Banggai Regency Ministry of Religion Office. From the results of the ANOVA (analysis of variance) test or F test, it was found that the F-count was 1568,386 and the F-table was 3.39. With this comparison, it means that it can be seen that the F-count = 1568,386 > F-table = 3.39, which means simultaneously positive and significant effect. The partial research results show that Supervision is the variable that has the most dominant and significant influence with a coefficient value of 3.257, which means that supervision has a dominant influence on Employee Performance (Y)